Development of computer code ADWITA and data library for the solution of transmutation chain equations and application to the analysis of nuclear fuel cycles. (15th December 2021) - Raj, Devesh; Kannan, Umasankari
Highlights: A computer program to study nuclear fuel cycle has been developed. The data files for the PHWR and AHWR have also been developed. The code has been verified using the analytical result, PIE data and available PHWR benchmarks. The 233 U conversion capability of AHWR (Th, 233 U) MOX fuel cycle, is illustrated. The build-up of activity and its extent in reprocessed uranium has been evaluated. Abstract: A fuel cycle analysis code, ADWITA (A ctivation, D ecay, W aste I ncineration and T ransmutation A nalysis) has been developed which can generate isotopic inventory, calculate radioactivity, and decay heat based on irradiation history. The code can be used for fuel cycle design and transmutation studies. The system of linearized transmutation chain equations is solved by application of Bateman series solution method and the matrix exponential method in which the matrix exponential is approximated by the exponential power series. The required data libraries for Pressurised Heavy Water Reactor (PHWR) and Advanced Heavy Water Reactor (AHWR) have also been developed. The code and the data have been validated using the analytical decay of 237 Np, the PHWR fuel cycle benchmark data available in IAEA TECDOC and experimental measurement of isotopic composition and decay heat in AECL report. The code has been applied for the analysis of fuel cycle of AHWR which has been designed for the utilisation of thorium as nuclear fuel on large scale and envisages fuel reprocessing. The application of code ADWITA and its library to AHWR has helped to understand the unique features of AHWR fuel cycle. It has been found that in AHWR the activity and decay heat due to actinides and fission product (FP) in both (Th, 233 U) MOX and (Th, Pu) MOX fuel is similar at the discharge but the activity and decay heat due to actinide takes over that due to FP in case of (Th, Pu) MOX earlier. The accumulation of uranium isotopes at the end of burnup in individual (Th, 233 U) and (Th, Pu) MOX fuel pin has been estimated which is an important input to the reprocessing of these fuels. The rise in activity after reprocessing due to presence of 232 U has also been estimated.